Factors Determining Purchase Intention and Behaviour of Consumers towards Luxury Fashion Brands In India: An Empirical Evidence - Priya Arora, Anu; Kishor, Nawal (British Journal of Marketing Studies, 2019)
The Luxury consumer goods market has enjoyed a significant rise during the last decade, predominantly in the emerging markets such as India. This research exhibits the adaptation and incorporation of the theory of planned behaviour (TPB) along with an external variable brand image to examine the determinants that influence Indian consumers’ purchase intention towards luxury fashion brands. The luxury goods of interest in this study are high-end personal fashion products including apparel, perfume, and accessories like handbags, shoes, watches. Data was collected in the form of a survey from 815 luxury goods users in Delhi-NCR and structural equation modeling was used to analyze the framework. Results revealed that all the four variables brand image, attitude, subjective norms and perceived behavioural control were found to have a positive relationship with purchase intention. Moreover positive influence of purchase intention is also found on actual purchase behaviour. Furthermore, both attitude and purchase behaviour are positively influenced by brand image. The findings of this research provides meaningful insights to marketers and managers to understand consumer behavior towards luxury and formulate marketing strategies to successfully market their products in India.